Ul[ca] Podwale Przedmiejskie 30, 32, 36 fot. Karol Nowaliński. - Nowaliński, Karol (1935- ). (1980)
Przedstawia ul. Podwale Przedmiejskie (wówczas Al. Leningradzka), po prawej budynki nr 30, 32, 36, ok. 1989 r.